LRRK2 Gene Variants Associated With a Higher Risk for Alcohol Dependence in Multiethnic Populations - Oliveira, Pablo Rafael Silveira; de Matos, Lorena Oliveira; Araujo, Nathalia Matta; Sant Anna, Hanaísa P.; da Silva e Silva, Daniel Almeida; Damasceno, Andresa K. Andrade; Martins de Carvalho, Luana; Horta, Bernardo L.; Lima-Costa, Maria Fernanda; Barreto, Mauricio Lima; Wiers, Corinde E.; Volkow, Nora D.; et al. (Frontiers in Psychiatry, 2021)
Background: Genetics influence the vulnerability to alcohol use disorders and among the implicated genes, three previous studies have provided strong evidences for the involvement of LRRK2 in alcohol dependence (AD). LRRK2 expression is broadly dysregulated in postmortem brain from AD humans, as well as in the brain of mice with alcohol dependent-like behaviors and in a Zebrafish model of alcohol preference. The aim of the present study was to evaluate the association of variants in the LRRK2 gene with AD in multiethnic populations from South and North America. Methods: Alcohol-screening questionnaires (such as CAGE and AUDIT) were used to determine individual risk of AD. Multivariate logistic regression analyses were done in three independent populations (898 individuals from Bambuí, Brazil; 3,015 individuals from Pelotas, Brazil; and 1,316 from the United States). Linkage disequilibrium and conditional analyses, as well as in silico functional analyses were also conducted. Results: Four LRRK2 variants were significantly associated with AD in our discovery cohort (Bambuí): rs4768231, rs4767971, rs7307310 and rs1465527. Two of these variants (rs4768231 and rs4767971) were replicated in both Pelotas and United States cohorts. The consistent association signal (at the LRRK2 locus) found in populations with different genetic backgrounds reinforces the relevance of our findings. Conclusion: Taken together, these results support the notion that genetic variants in the LRRK2 locus are risk factors for AD in humans.